Fonoaudiologia e saúde mental: experiência em equipe multiprofissional com portadores de transtornos mentais institucionalizados - Almeida, Beatriz Paiva Bueno de (2010)
The objective of this work is to characterize and analyze the speech developed at the Integrated Healthcare of Santa Rita do Passa Quatro - SP (CAIS-SR), an institution whose history was marked by the process of institutionalization of mental patients and then by Psychiatric Reform. The research is designed as a case study, with emphasis on research for a project of care group (group / choir Sabiá na Laranjeira ) conducted by the Speech Therapy in CAIS-SR. The research method combines survey of speech-language record of the activities carried out, which occurred between 2001 and 2006, interviews with professional teams of CAIS-SR and group patients Sabiá na Laranjeira about the presence of speech therapist throughout this period, and especially analysis of the group work done with patients of Sabiá na Laranjeira . To put the analysis the work of Speech Therapy in CAIS-SR, is presented key issues to care of patients with mental disorders, namely: the marks that isolation makes the life history of these subjects, the composition and relevance of inter-and multidisciplinary teams in mental health; social exclusion and the search for activities that help in building a new and more satisfactory social conditions for such subjects. In this sense, the dissertation points to the fact that the speech therapist, participating in teams of CAIS-SR, beyond to identify and treat speech pathology, should value and encourage communication and discursive circulation among patients and those with family members and society by increasing the use of language (verbal and nonverbal) and shedding light on the importance of communication, among other things: biopsychosocial rehabilitation; training of interpersonal bonds; legitimacy and social belonging of the subjects with mental disorders, which aligns public policies with anti-psychiatric ward and social reintegration